THE EFFECT OF INFORMATION OVERLOAD ON DECISION POSTPONEMENT MEDIATED BY DECISION DIFFICULTY ON GENERATION Z IN JEPARA - Zulkarnaen, Ahmad Ferdi; Roosdhani, Mohamad Rifqy (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research seeks to ascertain the impact of information overload on decision delay mediated by decision-making difficulties in Generation Z in Jepara. This study is quantitative on the population, namelyGeneration Z in Jepara by having chosen respondents complete surveys through the simple randomsampling method using the Rao Purba formula. The PLS-SEM approach was utilized to evaluate the 310samples used in this investigation using the Smart PLS version 4.0 application. The results of this studyindicate that information overload has a substantial and favorable impact on decision delay, informationOverload significantly and favorably affects decision-making difficulties, decision-making difficulties havea favorable and noteworthy impact on decision delay. information overload on decision delay mediated bydecision-making difficulties also has a positive relationship.